Cone-Beam Computed Tomography and Radiographs in Dentistry: Aspects Related to Radiation Dose - Diego Coelho Lorenzoni; Ana Maria Bolognese; Daniela Gamba Garib; Fabio Ribeiro Guedes; Eduardo Franzotti Sant'Anna (Hindawi Limited, 2012)
Introduction. The aim of this study was to discuss the radiation doses associated with plain radiographs, cone-beam computed tomography (CBCT), and conventional computed tomography (CT) in dentistry, with a special focus on orthodontics. Methods. A systematic search for articles was realized by MEDLINE from 1997-March 2011. Results. Twenty-seven articles met the established criteria. The data of these papers were grouped in a table and discussed. Conclusions. Increases in kV, mA, exposure time, and field of view (FOV) increase the radiation dose. The dose for CT is greater than other modalities. When the full-mouth series (FMX) is performed with round collimation, the orthodontic radiographs transmit higher dose than most of the large FOV CBCT, but it can be reduced if used rectangular collimation, showing lower effective dose than large FOV CBCT. Despite the image quality, the CBCT does not replace the FMX. In addition to the radiation dose, image quality and diagnostic needs should be strongly taken into account.